APPLICATION PROGRAMMING LANGUAGE C SEARCH FOR ERRORS RELATIVE VALUE AND LITERATURE IN practicum MATHEMATICAL pendulum CASE STUDY: BASIC PHYSICS LABORATORY STMIK JAKARTA STI&K - Melani Dewi Lusita (JAKSTIK Journal, 2004)
This writing describes how to find the value of relative error and the literature on experimentsconducted by the lab in the Laboratory of Basic Physics with Mathematical pendulummodule. The need for accurate data is needed. In the case of a mathematical pendulum labwork, data processing will be computerized using C language.